THE EFFECT OF RITATOON MEDIA USAGE TOWARD SCIENCE LEARNING OUTCOMES OF STUDENT WITH INTELLECTUAL DISABILITY - Denty Yanuarini; . Pramono (Department of Special Education, 2016)
Based on observations, there are problems in IPA learning outcomes of student with intellectual disability, which is still relatively low. It is caused by learning methods used are only as a mere lecture, self-employment, textual and less attractive media such as white board. The purposes were to describe: (1) science learning outcomes of grade VIII student with intellectual disability before using ritatoon media, (2) science learning outcomes of grade VIII student with intellectual disability after using ritatoon media, (3) the effect of ritatoon media usage toward science learning outcomes of grade VIII student with intellectual disability. This research used a single subject experimental design with Single Subject Research (SSR) method. Results showed that the baseline-1 values obtained was 55% - 65%, the intervention phase values obtained was 80% - 95%, baseline-2 phase values obtained was 90% - 95%. The conclusion was the use of ritatoon media usage gives effect toward the science learning outcomes on natural event materials.